Funcionalidad familiar y adherencia al tratamiento de tuberculosis pulmonar en usuarios atendidos en la IPRESS I – 4 Bellavista Nanay Iquitos 2024 - Cardenas Gonzales, Jenniffer Anailuj (2024)
The objective of this work was to determine the relationship between family functionality and adherence to pulmonary tuberculosis treatment in users treated at the IPRESS I - 4 Bellavista Nanay Iquitos 2024. The quantitative method was used with a non-experimental, descriptive, cross-sectional correlational design. The population was 78 users with pulmonary tuberculosis and the sample was made up of 65 users. The technique was the survey and the instruments were the Family Apgar: Questionnaire to evaluate family functionality and the Morisky-Green Pulmonary Tuberculosis Treatment Adherence Questionnaire. To analyze the data, the statistical software SPSS version 24.0 was used and to determine the correlation the Chi Square test (X2) with a significance level of α < 0.05 was used. The results show that 44.6% users presented moderate family dysfunction, 35.4% mild family dysfunction, 15.4% good family functionality and 4.6% severe family dysfunction. Regarding adherence to the treatment of pulmonary tuberculosis, 78.5% users were adherent and 21.5% were non-adherent. In conclusion, a significant statistical relationship was found between family functionality and adherence to pulmonary tuberculosis treatment p=0.002 (p<0.05).